FRI0175 Rates and predictors of radiographic sacroiliitis progression after central reading in patients with axial spondyloarthritis from the asas cohort: a 5-year follow-up study. (12th June 2018) - Protopopov, M.; Proft, F.; Sepriano, A.; Landewé, R.; van der Heijde, D.; Sieper, J.; Rudwaleit, M.; Poddubnyy, D.
Abstract : Background: In patients with axial spondyloarthritis (axSpA), radiographic progression of sacroiliitis is relatively slow, with only few predictors identified. Recently, an analysis of data from Ankylosing Spondylitis Assessment Society (ASAS) Cohort, based on local assessment of X-Rays, revealed a surprisingly high rate of regression from radiographic axSpA (r-axSpA) to non-radiographic axSpA (nr-axSpA). 1 Objectives: To analyse the rates and predictors for radiographic progression of sacroiliitis in patients with axSpA from the ASAS Cohort, based on the central reading of radiographs. Methods: Altogether 205 patients, who were included in the ASAS Cohort and diagnosed with axSpA by local rheumatologists, with baseline pelvic radiographs available for central reading, were included in the current study. Among them, 106 patients also had a pelvic radiograph at follow up (mean time to follow up 4.4±0.8 years). Images were independently assessed by 2 central readers (MP, FP), blinded for the chronology of the radiographs, according to the scoring system of the modified New York criteria (grade 0–4). In case of disagreement in classification (nr-axSpA or r-axSpA), the image was scored by an adjudicator (DP) that defined the final classification. In addition, we calculated a sacroiliitis sum score (0–8) based on scoring results of 2 (3) readers. The primary outcome was the proportion of patients with progression from nr-axSpA to r-axSpA at follow-up. Predictors of progression were investigated in univariable and multivariable logistic regression analyses. Results: Among 205 patients, 82 (40%) were classified as nr-axSpA, and 123 (60%) as r-axSpA at baseline. Among 106 patients with available baseline and follow-up radiographs, 49 (46, 2%) were classified as nr-axSpA, and 57 (53, 7%) as r-axSpA at baseline. The agreement between two primary readers in classification (either nr-axSpA or r-axSpA) was moderate to substantial (κ=0.54 at baseline and κ=0.63 at follow up); between local and central readers – poor to moderate (κ=0.18 at baseline and κ=0.58 at follow up). At follow up, 8 (7, 5%) patients progressed from nr-axSpA to AS, while 6 (5, 7%) were reclassified from AS to nr-axSpA, resulting in net progression of 1, 9%. The sacroiliitis sum score increased in 43 (40, 6%) patients, decreased in 21 (19, 8%) and did not change in 42 (39, 6%). Logistic regression analysis showed an association of active and chronic changes on MRI at baseline, already existing structural damage in the sacroiliac joints (sacroiliitis sum score) at baseline and younger age with higher odds for progression from nr-axSpA to r-axSpA. Conclusions: There was a low but still detectable progression from nr-axSpA to r-axSpA after up to 5 years of follow-up in the ASAS cohort. Presence of active and chronic changes on MRI, initial structural damage on radiographs, and younger age at baseline were associated with a higher odds for progression from nr-axSpA to r-axSpA. Reference: [1] Sepriano A, et al. Ann Rheum Dis2016;75:1262–1263. Acknowledgements: The research was supported by 2016 ASAS Research Internship Grant. Disclosure of Interest: None declared